PROCESS OF COMMUNITY UNIFICATION AND PROBLEMS OF DEVELOPMENT OF SETTLEMENT PATTERN IN BORDERLANDS, MOUNTAINOUS AND HIGH-MOUNTAINOUS AREAS (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Over the past two decades, the problem of improving the administrativeterritorial division of RA at the local level has been in the focus of attention of researchers. The article presents suggestions for reorganization of unified communities in the border mountainous and high-mountainous regions of RA, considering the features of the territorial structure settlement of these areas at the local level.
Keywords: unified communities; decentralization; administrative-territorial division; settlement pattern; transport accessibility; local centre